2023
DOI: 10.1029/2022gl102127
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Carbonates, Oxychlorines, and Chlorine Generated by Heterogeneous Electrochemistry Induced by Martian Dust Activity

Abstract: Heterogeneous electrochemistry induced by Martian dust activity is an important type of atmosphere‐surface interaction that affects geochemical processes at the Martian surface and in the Martian atmosphere. We have experimentally demonstrated that heterogeneous electrochemistry stimulated by mid‐strength dust events can decompose common chloride salts, which is accompanied by the release of chlorine atoms into the atmosphere and the generation of (per)chlorates (chlorates and perchlorates) and carbonates. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…One type of formation processes involves a relatively recent formation at low water chemical activity and possibly low temperature by rapid olivine carbonation and/or catalysis by heterogeneous electrochemistry (Garenne, 2013; Kelemen, 2020; Shaheen et al., 2010; Wang et al., 2022). Such processes rely on gas‐surface interactions and should form carbonates preferentially in the first few micrometers to tens of micrometers at the surface.…”
Section: Discussionmentioning
confidence: 99%
“…One type of formation processes involves a relatively recent formation at low water chemical activity and possibly low temperature by rapid olivine carbonation and/or catalysis by heterogeneous electrochemistry (Garenne, 2013; Kelemen, 2020; Shaheen et al., 2010; Wang et al., 2022). Such processes rely on gas‐surface interactions and should form carbonates preferentially in the first few micrometers to tens of micrometers at the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Research on in situ plasma and UV spectra monitored during ESD revealed that CO 2 + , CO + , O I , and O 3 are generated in dry CO 2 during the ESD process. The chemical reactions were inferred as follows: (M = Mg or K. Cl I marks the first excited state of the Cl atom, and M* marks the excited cation) normale + normalM Cl Cl normalI + normalM * Cl normalI + ( O I , O II , O 3 ) + normalM * normalM ClO 3 MClO 3 + ( O I , O II , O 3 ) normalM ClO 4 …”
Section: Resultsmentioning
confidence: 99%
“…Research on in situ plasma and UV spectra monitored during ESD revealed that CO 2 + , CO + , O I , and O 3 are generated in dry CO 2 during the ESD process. The chemical reactions were inferred as follows: (M = Mg or K. Cl I marks the first excited state of the Cl atom, and M* marks the excited cation) …”
Section: Resultsmentioning
confidence: 99%
“…Under most circumstances, the present atmosphere of Mars is too tenuous to support lightning. However, electrostatic emissions that affect chemical changes, for example, in the chlorine cycle, have been observed to be associated with recent martian dust storm activity (Ruf et al., 2009; Wang et al., 2023). However, severe lightning storms may have been associated with episodes of explosive volcanism, which are thought to have generated extensive, dynamic eruptive ash clouds (Brož & Hauber, 2012, 2013; Brož et al., 2021; Halevy & Head, 2014; L. Wilson & Head, 1994).…”
Section: Systematic Survey Of Paragenetic Modesmentioning
confidence: 99%
“…(2009); 124 = Wang et al. (2023); 125 = L. Wilson and Head (1994); 126 = Brož et al. (2021); 127 = Tomioka and Miyahara (2017); 128 = Tschauner (2019); 129 = El Goresy et al.…”
Section: Introductionmentioning
confidence: 99%